The Negro soldier - Capra, Frank, 1897-1991.; United States. War Department (Los Angeles, Calif. : International Historic Films, 2006)
Traces the role of the Negro soldier in American history from 1776 to 1944, and shows the accomplishments of Negro troops.
Issued in 1943 as a motion picture.
Music, Army Air Forces Orchestra.
Keywords: African American soldiers -- History; United States. -- Army -- African American troops -- History; United States. -- Army; African American soldiers; Armed Forces -- African American troops; History